Prophylaxis of fat embolism syndrome: a current analysis - Renato da Silva Freitas; Ruth Graf; Maria Cecilia Closs Ono; Ivan Maluf Junior; Isis Nasser; Priscilla Balbinot; Patricia Bigolin; Marlon Augusto Camara Lopes; William Massami Itikawa (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: To analyze data from the internet on deaths from fat embolism, time of onset, and other information that could determine current reality in Brazil regarding fat embolism syndrome incidence and any ,media repercussions, and also to review methods of prevention and what are the best methods available to treat this disease. METHODS: A Google search was conducted from January 2000 to January 2014 using the keywords "plastic surgery" and "death." We included and reviewed articles containing the words "embolism", "fat embolism" and "complications in (or of) plastic surgery". RESULTS: We included 235 relevant news stories over the 14 included years. There were 45 cases of death related with plastic surgery that offered few data for individualization. Of these patients, 44 were women. Possible causes mentioned were pulmonary embolism (five cases), perforation of viscera (four cases), malignant hyperthermia (three cases), anesthesia (two cases), anaphylactic shock (two cases), fat embolism (one confirmed case), and "other" (five cases). CONCLUSION: Guidelines to prevent fat embolism in plastic surgery are needed, however, there is also the need of more evidence based studies to understand more clearly what methods are best.